44 Core-shell nanospheres for pH-responsive release of anticancer drugs and near-infrared imaging. (19th December 2016) - Jin, Yuanbao; Yuan, Ruwen; Jin, Yuanyuan; Wang, Liying; Fu, Jia; Zhao, Mingzhi; Meng, Fanxin
Abstract : Objectives: Nanoscaled drug carriers with pH-responsiveness have attracted extensive interest in view of the acidic environment in cancerous cells. Rapid response to pH changes plays a key role in efficient intracellular drug release. In addition, real-time tracking of drug carriers is important for understanding distribution and targeted accumulation of the drug carriers. This work aims at developing silver selenide quantum dots (Ag2 Se QDs)@carboxymethyl chitosan (CMCS) core-shell nanospheres with encapsulated paclitaxel (PTX) for cancer therapy and bioimaging. Methods: Oleic acid-capping Ag2 Se QDs were synthesized by a one-pot strategy, washed with ethanol, and obtained by centrifugation. The as-synthesized Ag2 Se QDs were reacted with N-hydroxysuccinimide and conjugated with CMCS at the amino sites. In an aqueous solution of PTX, the hydrophobic oleoyl groups tended to aggregate locally and entrap PTX by hydrophobic interaction, spontaneously producing Ag2 Se QDs (PTX)@CMCS nanospheres. Results: By conjugating the oleic acid-capping Ag2 Se QDs with pH-sensitive CMCS at a degree of substitution (DS) of 13%, biocompatible core-shell nanospheres loaded with PTX were successfully prepared, which had an average size of 36.3 ± 0.2 nm. The drug loading content (DLC) and drug loading efficiency (DLE) for the PTX was 5.01 ± 0.8% and 52.4 ± 3.2%, respectively. The PTX release half-life was 4.1 hours under conditions resembling the intracellular environment of cancerous cells (37°C, pH 5.0). Conclusions: Core-shell structured Ag2 Se QDs (PTX)@CMCS nanospheres capable of releasing PTX in an acidic environment and emitting NIR fluorescence under NIR laser excitation were synthesized and characterized. The hydrophobic oleoyl groups entrapped PTX via hydrophobic interaction and the oleoyl-CMCS chains were extended at lowered pH to release the otherwise encaged drug. In addition, the encapsulated Ag2 Se QDs can emit bright NIR fluorescence for bioimaging by which nanosphere distribution in a patient can be monitored. This study provides a new approach for developing nanocomposite drug carriers for cancer therapy.